2016
DOI: 10.3390/molecules21060763
|View full text |Cite
|
Sign up to set email alerts
|

Bioaccumulation and Subchronic Toxicity of 14 nm Gold Nanoparticles in Rats

Abstract: Colloidal suspensions of 14 nm gold nanoparticles (AuNPs) were repeatedly administered intravenously at three dose levels (0.9, 9 and 90 µg) to male Sprague Dawley rats weekly for 7 weeks, followed by a 14-day washout period. After sacrificing, the amount of gold was quantified in the liver, lungs, spleen, skeleton and carcass using neutron activation analysis (NAA). During the study, preand post (24 h) administration blood samples were collected from both the test and control groups, the latter which received… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
36
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(42 citation statements)
references
References 47 publications
3
36
0
1
Order By: Relevance
“…Elberry, et al (2010) who reported that CCl 4 is an important toxin which prompts liver injury by elevating serum levels of liver enzymes such as ALT, AST, ALP (16) and also reported the severity of liver damage [16]. Our results revealed that AST, ALT and ALP in group CCl 4 +AuNP did not show any significant differences with those of group CCL 4 and are then in in line with the findings by Clinton Rambanapasi, et al (2016) who reported that the indicators of liver damage, AST and ALT showed no significant differences between the control and experimental groups [18]. The results in the present study were promised by Shu Dong, et al (2016) who reported that toxicological mechanisms of CCl 4 -induced liver fibrosis may be related to multi biological manner mechanisms for CCl 4 detoxication in the liver [5].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Elberry, et al (2010) who reported that CCl 4 is an important toxin which prompts liver injury by elevating serum levels of liver enzymes such as ALT, AST, ALP (16) and also reported the severity of liver damage [16]. Our results revealed that AST, ALT and ALP in group CCl 4 +AuNP did not show any significant differences with those of group CCL 4 and are then in in line with the findings by Clinton Rambanapasi, et al (2016) who reported that the indicators of liver damage, AST and ALT showed no significant differences between the control and experimental groups [18]. The results in the present study were promised by Shu Dong, et al (2016) who reported that toxicological mechanisms of CCl 4 -induced liver fibrosis may be related to multi biological manner mechanisms for CCl 4 detoxication in the liver [5].…”
Section: Discussionsupporting
confidence: 91%
“…Groups 2 and 3 as experimental were injected with CCl 4 liquefied in fluid paraffin (1 mL/kg b.w) for a period of 42 days intraperitonealy (ip), while control group (c) received saline intraperitonealy and also fluid paraffin (1 mL/kg body weight) subcutaneously every other day in trial period [16,17]. On the seventh week of the study, group 3 received additional colloidal suspensions of 20 nm gold nanoparticles (AuNP) intraperitonealy, repeatedly administered in saline solution at dose levels of 90 µg for three days [18]. All animals had free access to water and food during the trial period and were sustained in a room at 23 ± 2°C temperature of fixed 12: 12-hours synthetic light/dark period (6 am to 6 pm), with humidity of 45% -65%.…”
Section: Methodsmentioning
confidence: 99%
“…In fact, in certain taxa, some evidence indicates that AuNPs are toxic, whereas other studies indicate they are not (Rambanapasi et al . ). Toxicity studies are not always systematic, which explains the contradictory results (Chen et al .…”
Section: Toxicity Of Aunpsmentioning
confidence: 97%
“…[29] podawali szczurom dożyl-nie zawiesinę nanocząstek złota o średnicy 14 nm raz na tydzień przez 7 tygodni (w dawce 2,25 μg/kg mc., 22,5 μg/kg mc. lub 0,22 mg/kg mc.).…”
Section: Efekty Toksyczne Nanoobiektów Złotaunclassified